A Contrastive Analysis Of Phonetic Realization Of Consonant Cluster In English And Arabic Languages (Journal of the College of Basic Education, 2024)
The phonetic realization of consonant clusters presents a challenge for studies on speech production. English and Arabic are two dialects that vary enormously in the scope of the syllable structure designs they make utilization of. An immediate conclusion to this is the distinction in the degree to which every language licenses consonant groups. As a rule, Arabic is a language that is poor in group when contrasted with English. Hence incredible impedance is normal when English expect the status of the objective language for the local speakers of Arabic. The issue of consonant groups is, truth is told, a territory deserving of examination at whatever point contrastive Arabic-English investigations are intended.